Risk factors for mortality in end-stage kidney disease patients under online-hemodiafiltration: three-year follow-up study. (17th August 2016) - Sousa-Martins, Pedro de; Moura, Alexandra; Madureira, José; Alija, Pablo; Oliveira, José Gerardo; Lopez, Martin; Filgueiras, Madalena; Amado, Leonilde; Sameiro-Faria, Maria; Miranda, Vasco; Mesquita, Edgar; Teixeira, Laetitia; et al.
Abstract: The aim of this work was to evaluate the predictors of mortality in a group of end-stage kidney disease (ESRD) patients under dialysis, by performing a three-year follow-up study. From the 236 patients included in this study, 54 patients died during the three-year follow-up period. Our data showed that the risk of death was higher in patients presenting lower levels of mean cell hemoglobin concentration, transferrin, and albumin. Our study showed that poor nutritional status and an inflammatory-induced iron depleted erythropoiesis are important factors for mortality in these patients.